Polyamine Induction in Postharvest Banana Fruits in Response to NO Donor SNP Occurs via l-Arginine Mediated Pathway and Not via Competitive Diversion of S-Adenosyl-l-Methionine - Veeresh Lokesh; Girigowda Manjunatha; Namratha S. Hegde; Mallesham Bulle; Bijesh Puthusseri; Kapuganti Jagadis Gupta; Bhagyalakshmi Neelwarne (MDPI AG, 2019)
Nitric oxide (NO) is known to antagonize ethylene by various mechanisms; one of such mechanisms is reducing ethylene levels by competitive action on S-adenosyl-L-methionine (SAM)—a common precursor for both ethylene and polyamines (PAs) biosynthesis. In order to investigate whether this mechanism of SAM pool diversion by NO occur towards PAs biosynthesis in banana, we studied the effect of NO on alterations in the levels of PAs, which in turn modulate ethylene levels during ripening. In response to NO donor sodium nitroprusside (SNP) treatment, all three major PAs viz. putrescine, spermidine and spermine were induced in control as well as ethylene pre-treated banana fruits. However, the gene expression studies in two popular banana varieties of diverse genomes, Nanjanagudu rasabale (NR; AAB genome) and Cavendish (CAV; AAA genome) revealed the downregulation of SAM decarboxylase, an intermediate gene involved in ethylene and PA pathway after the fifth day of NO donor SNP treatment, suggesting that ethylene and PA pathways do not compete for SAM. Interestingly, arginine decarboxylase belonging to arginine-mediated route of PA biosynthesis was upregulated several folds in response to the SNP treatment. These observations revealed that NO induces PAs via l-arginine-mediated route and not via diversion of SAM pool.